Raw data on metal accumulation and biochemical and physiological biomarker data in Nile tilapia exposed to settleable atmospheric particulate matter (SePM) - Adorno, Henrique Aio (2023)
Raw data from blood and heart samples of Nile tilapia (Oreochromis niloticus) exposed to settleable atmospheric particulate matter (SePM) from an industrial area.